The Yield Gap Maize under Intensive Cropping System in Central Java - Aristya, Vina Eka; Samijan, Samijan (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
The study aimed to estimate the level of the yield gaps of maize in major producing areas, point out the causes of yield gaps in farmers’ maize fields, and identify opportunities to the existing yield gaps through management practices of maize production in Central Java. This is the strategy for closing the existing yield gaps to achieve food self-sufficiency in agricultural land. Methods to estimates the yield gaps should cover data sources on physical conditions (weather and soil), management practices, and smallholder shapes. The relevant methods for estimating actual yields (Ya), potential (Yp), and water-limited (Yw) were compared. The yield gaps of maize under intensive cropping systems in rainfed ecosystems resulted in significant differences in all cultivation situations. The lowland rainfed maize showed Ya, Yp, and Yw values of 5.57, 12.83, and 12.47 ton/ha, respectively. The major causes of the yield gaps include variety, land preparation, and water issues concerned with the limited water inputs.